Developmental evaluation of atypical auditory sampling in dyslexia: Functional and structural evidence. Issue 12 (10th September 2015) - Lizarazu, Mikel; Lallier, Marie; Molinaro, Nicola; Bourguignon, Mathieu; Paz‐Alonso, Pedro M.; Lerma‐Usabiaga, Garikoitz; Carreiras, Manuel
Abstract: Whether phonological deficits in developmental dyslexia are associated with impaired neural sampling of auditory information at either syllabic‐ or phonemic‐rates is still under debate. In addition, whereas neuroanatomical alterations in auditory regions have been documented in dyslexic readers, whether and how these structural anomalies are linked to auditory sampling and reading deficits remains poorly understood. In this study, we measured auditory neural synchronization at different frequencies corresponding to relevant phonological spectral components of speech in children and adults with and without dyslexia, using magnetoencephalography. Furthermore, structural MRI was used to estimate cortical thickness of the auditory cortex of participants. Dyslexics showed atypical brain synchronization at both syllabic (slow) and phonemic (fast) rates. Interestingly, while a left hemispheric asymmetry in cortical thickness was functionally related to a stronger left hemispheric lateralization of neural synchronization to stimuli presented at the phonemic rate in skilled readers, the same anatomical index in dyslexics was related to a stronger right hemispheric dominance for neural synchronization to syllabic‐rate auditory stimuli. These data suggest that the acoustic sampling deficit in development dyslexia might be linked to an atypical specialization of the auditory cortex to both low and high frequency amplitude modulations. Hum Brain Mapp 36:4986–5002, 2015 . © 2015 Wiley Periodicals, Inc.